ANALISIS PROSES REKRUTMEN DALAM MENINGKATKAN KINERJA KARYAWAN PADA PT. SUPRA BOGA LESTARI, TBK. JAKARTA BARAT - Mawarni, Widya; Sularmi, Lili (Journal of Research and Publication Innovation, 2024)
This research aims to analyze and describe the employee recruitment process at PT. Supra Boga Lestari, Tbk. West Jakarta. This research is a qualitative research. Data collection uses interview techniques with one of the employees (as a resource person) who works at PT. Supra Boga Lestari, Tbk.